Multimodal transport in South Africa - Clulow, Jeb Anthony (Department of Commercial Law, 2023)
Both the physical and the contractual aspects of multimodal transport have caused and continue to cause significant legal problems. Physical multimodal transport, is the carriage of goods from place A to place B by more than one mode of transport. Contractual multimodal transport takes place when a single person assumes responsibility for the goods throughout the entire carriage from A to B regardless of whether he is physically involved in the carriage of the goods. Physical multimodal transport can and often does stand alone. In such a case, one usually finds that a freight forwarder contracts, as agent of the consignor, with a number of carriers for carriage by a number of different modes of transport. The basis of physical multimodal transport has been containerization, which involves inter alia carriage on deck. The law has had difficulty in accepting the weather deck of a ship as a legitimate place for the carriage of cargo.